Inextensible Flows of Spacelike Curves on Spacelike Surfaces according to Darboux Frame in M13 - Bas, Selcuk; Korpinar, Talat (Soc Paranaense Matematica, 2013)
In this paper, we study inextensible flows of spacelike curves on oriented spacelike surfaces in M-1(3). We give necessary and sufficient conditions for inextensible flows of spacelike curves on oriented spacelike surfaces in M-1(3).
Keywords: Inextensible flows; Darboux Frame; Curvatures